Coagulation abnormalities of sickle cell disease: Relationship with clinical outcomes and the effect of disease modifying therapies. Issue 4 (July 2016) - Noubouossie, Denis; Key, Nigel S.; Ataga, Kenneth I.
Abstract: Sickle cell disease (SCD) is a hypercoagulable state. Patients exhibit increased platelet activation, high plasma levels of markers of thrombin generation, depletion of natural anticoagulant proteins, abnormal activation of the fibrinolytic system, and increased tissue factor expression, even in the non-crisis "steady state." Furthermore, SCD is characterized by an increased risk of thrombotic complications. The pathogenesis of coagulation activation in SCD appears to be multi-factorial, with contributions from ischemia–reperfusion injury and inflammation, hemolysis and nitric oxide deficiency, and increased sickle RBC phosphatidylserine expression. Recent studies in animal models suggest that activation of coagulation may contribute to the pathogenesis of SCD, but the data on the contribution of coagulation and platelet activation to SCD-related complications in humans are limited. Clinical trials of new generations of anticoagulants and antiplatelet agents, using a variety of clinical endpoints are warranted.